Fever and Skin Involvement at Diagnosis Predicting the Intractable Langerhans Cell Histiocytosis: 40 Case-Series in a Single Center. Issue 3 (April 2018) - Kobayashi, Tetsuko; Koga, Yuhki; Ishimura, Masataka; Nakashima, Kentaro; Kato, Wakako; Ono, Hiroaki; Sonoda, Motoshi; Eguchi, Katsuhide; Fukano, Reiji; Honjo, Satoshi; Oda, Yoshinao; Ohga, Shouichi
Abstract : Langerhans cell histiocytosis (LCH) occurs as a clonal disease with enigmatic immune responses. LCH patients occasionally present with fever, although the significance remains elusive. We investigated the predicting factors for developing intractable disease of refractory and/or reactivated LCH. In total, 40 pediatric LCH patients managed in Kyushu University from 1998 to 2014 were enrolled. The medical records were analyzed retrospectively. Sixteen patients suffered from multisystem (MS) LCH involving risk organs (ROs) (n=4) or not (n=12). In total, 24 patients had single-system LCH affecting bone (multi n=8, single n=13), skin (n=2), or lymph node lesions (n=1). Eight patients had the intractable disease of 7 MS or 1 multibone LCH. Two patients died from MS LCH with or without RO involvement. Ten patients showed persistent fever (>38°C) at onset. Intractable cases had fever, RO and skin involvement, leukocytosis, coagulopathy, microcytic anemia, higher levels of soluble interleukin-2 receptor and C-reactive protein, more frequently at diagnosis. Multivariate analysis indicated that fever and skin lesions at diagnosis were independently associated with the intractability (odds ratio: fever, 35.5; 95% confidence interval, 3.0-1229.1; skin lesions, 24.6; 95% confidence interval, 1.9-868.7). Initial fever and skin involvement might predict the development of intractable and fatal-risk LCH even without the RO involvement. Abstract : Supplemental Digital Content is available in the text.